DEGASSING OF METALS AND METALLOIDS FROM ERUPTING SEAMOUNT AND MID-OCEAN RIDGE VOLCANOES: OBSERVATIONS AND PREDICTIONS - Rubin K. (My University, 1997)
Recently, it has been reported that the element polonium degasses from mid-ocean ridge and seamount volcanoes during eruptions. Published and new observations on other volatile metal and metalloid elements can also be interpreted as indicating significant degassing of magmatic vapors during submarine eruptions. This process potentially plays an important role in the net transfer of chemical elements from erupting volcanoes to seawater in addition to that arising from sea floor hydrothermal systems. In this paper, a framework is constructed for predicting and assessing semiquantitatively the potential magnitude and chemical fingerprints in the water column of metal and metalloid degassing using (1) predictions from a summary of element volatilities during mafic subaerial volcanism worldwide and (2) limited data from submarine volcanic effusives. The latter include analyses of polonium and trace metals in near-volcano water masses sampled following a submarine eruption at Loihi seamount, Hawaii (1000 m bsl) in 1996. The element volatility predictions and observations show good agreement, considering the limited dataset. Some of the highest volatility main group and transition element enrichments in seawater over Loihi are predicted by the degassing mass transfer model I present. When expanded to cover all submarine volcanic activity, it is predicted that exit fluxes of these elements are up to 102–103 greater by degassing than by normal MOR hydrothermalism. In contrast, MOR exit fluxes of low volatility alkali and alkaline earth elements are likely 102–106 greater from hydrothermal inputs. Degassing inputs to the ocean are probably highly episodic, occurring almost entirely during eruptions; these are times of enhanced and abnormal hydrothermalism as well. Although major hydrothermal and degassing events may not be chemically recognizable in real water masses as wholly distinct entities, it is nevertheless possible to predict to what extent each process flavors the effluents of the other. Degassing at mid-ocean ridges may explain a variety of observations previously ascribed to complexities occurring during hydrothermal venting and/or fluid ascent in the buoyant hydrothermal plumes above ridges.